2022
DOI: 10.1007/s00167-022-07048-6
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve in robotic assisted knee arthroplasty is flattened by the presence of a surgeon experienced with robotic assisted surgery

Abstract: Purpose The purpose of this study was to investigate the learning curve associated with robotic assisted knee arthroplasty (RAS KA). Therefore, the evaluation of the influence of an experienced surgeon on the overall team performance of three surgeons regarding the learning curve in RAS KA was investigated. It was hypothesized that the presence of an experienced surgeon flattens the learning curve and that there was no inflection point for the learning curve of the surgical team. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…In terms of surgical time, most literature reports that MAKO RATKA achieves steady-state time neutrality after 7-80 cases [41,42]. Similar to the NAVIO RATKA results in this study, two studies have reported a continued decrease in MAKO RATKA surgical time without identiication of an inlection point up to 1 year after implementation of the new technology in clinical practice [19,33]. The results of this study have implications for clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…In terms of surgical time, most literature reports that MAKO RATKA achieves steady-state time neutrality after 7-80 cases [41,42]. Similar to the NAVIO RATKA results in this study, two studies have reported a continued decrease in MAKO RATKA surgical time without identiication of an inlection point up to 1 year after implementation of the new technology in clinical practice [19,33]. The results of this study have implications for clinical practice.…”
Section: Discussionsupporting
confidence: 82%
“…Pannu et al demonstrated 110 cases are needed to finally achieve the planned limb alignment when MAKO RAS system is utilized, seemingly aMA, although not explicitly described in the study 22 . In the present study, 20 initial cases were excluded due to the initial learning curve, but the results observed match previous learning curve studies demonstrating little to no learning curve in terms of implant position 13,23,24 . Winnock de Grave demonstrated superior outcomes of inverse kinematic when compared to aMA 7 .…”
Section: Accepted Manuscriptsupporting
confidence: 77%
“…Inclusion criteria were: TKA either using CAS or RAS between 01/2022 and 05/2022. Exclusion criteria were: First 20 cases using RAS due to the learning curve since a RASexperienced surgeon was not present 13 and cases where functional alignment was utilized This article is protected by copyright. All rights reserved.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the promising results of R-TKA, there are also some concerns associated with the regular usage of robotic surgery, as many authors and opponents of robotic TKA cite increased surgery times and costs [ 44 , 45 ]. However, several studies have demonstrated a relatively short learning curve regarding the duration of surgery, with similar operation room time for R-TKA compared to manual instrumentation after 10 to 20 cases [ 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%